Soybean reproductive physiology as affected by sublethal rates of auxin mimic herbicides - Koffi Badou-Jeremie Kouame; Benjamin C. Thrash; Nick R. Bateman; Gus M. Lorenz; Thomas R. Butts (Scientific Reports)
Abstract Auxin mimic herbicide off-target movement is a major environmental concern; it can affect crop yield, endangered species, and pollinator foraging sources. For the first time, the effects of sublethal rates of four auxin mimic herbicides (2,4-D, dicamba, florpyrauxifen-benzyl, and quinclorac) were evaluated to improves our understanding of how these herbicides negatively impact a pollinator nutritional source of pollinators. Dicamba and florpyrauxifen-benzyl applied at 1/100x of the labeled rate (5.60 g ae ha− 1 dicamba and 0.30 g ha− 1 florpyrauxifen-benzyl) reduced the total number of soybean reproductive organs (flowers and pods) by 31% and 27%, respectively, compared to the nontreated control (n = 373). Exposure to the same rates reduced pollen grains per anther by 25% and 18%, respectively, compared to the nontreated control (n = 338). The maximum reproductive per plant biomass accumulated was reduced by 30% from sublethal rates of dicamba and florpyrauxifen-benzyl applications at 1/100x compared to the nontreated control (23 g plant-1). An application of dicamba and florpyrauxifen-benzyl at 1/100x resulted in a 24% and 11% reduction in grain yield, respectively, compared to the nontreated control (3063 kg ha-1). While soybean reproductive organs, pollen grains, and yield were reduced from dicamba and florpyrauxifen-benzyl, 2,4-D and quinclorac had no impact on soybean physiological responses in this study. These results reinforce the idea that exposure to auxin mimic herbicides could reduce the quantity of pollen which could negatively affect pollinators’ foraging sources. Albeit, this relationship is highly dependent on the specific herbicide active ingredient and rate. This trend could have major implications for commercial bee keepers regarding the health of their bees near soybean fields that had drift damage. Proactive mitigation strategies are required when using auxin mimic herbicides to prevent off-target movement and subsequent negative consequences for pollinator foraging sources.